Training, Compensation, and Job Performance: A Critical Review of their Relationship - Yulius, Yunalfian; Yulius, Yunirsan (International Review of Management and Marketing, 2019)
Issues that affect performance PMPTSP Service employee compensation is not balanced with energy, thought, and time has been sacrificed by the employee. Compensation awarded tends to be based groups and not based on the performance of employees. In this study the performance of employees is not optimal compensation allegedly due to the application of the less in accordance with the provision of education and training has not done well. Performance of employees who tend to be less than optimal, judging from the results of a preliminary survey in which 45% of respondents have not been able to finish every job on time. 60% of employees think cannot focus on finishing the job when the boss is not in place. Given the nature of this research is descriptive and verification, Keywords: job performance, compensation, training. JEL Classifications: O32, M54, N75 DOI: https://doi.org/10.32479/irmm.8839